A near-infrared light-controlled, ultrasensitive one-step photoelectrochemical detection of dual cell apoptosis indicators in living cancer cells. Issue 60 (26th June 2020) - Zheng, Ying-Ning; Xiong, Cheng-Yi; Zhuo, Ying; Chai, Ya-Qin; Liang, Wen-Bin; Yuan, Ruo
Abstract : The proposed near-infrared (NIR) light-controlled, one-step photoelectrochemical (PEC) strategy could simultaneously detect cell apoptosis indicators, phosphatidylserine (Pho) and sodium potassium adenosine triphosphatase (Sat), on living cancer cells. Abstract : Here, a near-infrared (NIR) light-controlled, ultrasensitive one-step photoelectrochemical (PEC) strategy was constructed to simultaneously detect cell apoptosis indicators, phosphatidylserine (Pho) and sodium–potassium adenosine triphosphatase (Sat), on living cancer cells. Using NIR light as excitation, the signal probe methylene blue (Tagkinetic ) could be released, leading to a gradually decreased photocurrent signal I kinetic ; meanwhile, the photocurrent I stable of the signal probe carbon quantum dots (Tagstable ) remained stable. The simultaneous detection of Pho and Sat could be achieved based on rapid one-step PEC detection under single NIR light with the assistance of a smart signal decryption strategy with I kinetic and I stable . Importantly, this proposal provides more effective drug candidates with milder pharmaceutical effect but improved safety.